Una lectura del consumo a partir del espectro contemporáneo de enajenación cultural (2020)
This article aims to situate and criticize the problems that can arise from consumption. In view of this purpose, the philosophical analyses of the thinkers of the first generation of the Frankfurt School stand out. Their studies have made it possible to understand the ambiguities and social consequences of the consumerist phenomenon. In this way, the present work seeks, at first, a singular affinity between the philosophical assumptions of Horkheimer, Marcuse and Fromm and then to integrate and update them in total synchrony with the contemporary analyses of the postmodern thinker Gilles Lipovetsky. All this allows us to glimpse, explore and understand the problems of cultural alienation, the background of advertising and the permutation of use value in times of surplus consumption.